2019
DOI: 10.1038/s41433-019-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between patient-reported outcomes after enucleation and proton beam radiotherapy for uveal melanomas: a 2-year cohort study

Abstract: Background Uveal melanomas affect 2-8 per million Europeans each year. Approximately 35%, are treated by enucleation. Proton beam radiotherapy (PBR) can be an eye-conserving alternative to enucleation for patients who wish to retain the eye. Both treatments have adverse effects, and it is difficult for clinicians and patients to make fully informed choices between them because the relative effects of enucleation and PBR on patient-reported outcomes are unknown. Methods We compared differential effects of enucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…First, previous studies included different treatment strategies; second, data acquisition was inhomogeneous, with respect to the follow-up strategy; and third, some selected different questionnaires. For example, Hope-Stone et al did not report QLQ-C30 data, but showed similar results regarding "ocular irritation" and "worry about recurrence" at 6 months after treatment [13,14]. However, in that study, no pre-treatment assessment data were available to evaluate treatment-related changes over time.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…First, previous studies included different treatment strategies; second, data acquisition was inhomogeneous, with respect to the follow-up strategy; and third, some selected different questionnaires. For example, Hope-Stone et al did not report QLQ-C30 data, but showed similar results regarding "ocular irritation" and "worry about recurrence" at 6 months after treatment [13,14]. However, in that study, no pre-treatment assessment data were available to evaluate treatment-related changes over time.…”
Section: Discussionmentioning
confidence: 94%
“…Summary tables including all correlation heatmaps, final multiple linear regression models and figures on marginal means are provided as an attachment to this article (Additional files 1, 2, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton therapy is increasingly available for the treatment of uveal melanomas and is a valuable alternative for enucleation. Proton therapy offers good local tumour control, eye preservation and for some patients, even visual acuity preservation, which is important for functioning and quality of life [ 48 ]. Future studies should aim to further improve visual outcomes and reduce side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Proton beam radiotherapy might be an option in contrast to enucleation in patients who don’t agree to enucleation. 21 Regardless of revolutionary enucleation treatment, the quantity of patients who create metastases and end lethally is still as high as half. 22 There stays a worry that if choroidal dangerous melanoma is little and undiscovered in light of its size, it might make the tumor metastasize and the patient will kick the bucket sooner contrasted with if the tumor is bigger and conclusion and treatment quicker.…”
Section: Discussionmentioning
confidence: 99%